Peran mediasi profitabilitas dimoderasi leverage pada kepemilikan institusional terhadap nilai perusahaan: perusahaan batu bara Indonesia - Widigdya, Singgih; Akhmadi, Akhmadi; Ichwanudin, Wawan (Universitas Muhammadiyah Magelang, 2024)
In this study, we look at how institutional ownership affects the Price to Book Value (PBV) of Indonesian coal mining companies. Return on Assets (ROA) is the mediating variable, and Debt to Equity Ratio (DER) is the moderating variable. The study is highly relevant given the dynamic changes in financial markets, the increasing dominance of institutional investors, and the challenges associated with debt management. Additionally, regulatory changes and the pressure to enhance shareholder value necessitate an understanding of how institutional ownership, financial performance, and leverage influence company value. Using financial information from Indonesian coal mining companies that were listed between 2018 and 2023 on the Indonesian Stock Exchange, the analysis was conducted using SPSS and the Hayes Process Macro Model 58. The findings indicate that institutional ownership significantly increases firm value (PBV) through better management and stricter supervision. DER, as a moderating variable, emphasizes the importance of good debt management. The positive coefficient of financial performance on firm value indicates that better financial performance contributes to increased firm value. Overall, institutional ownership is more effective in directly enhancing firm value than through the mechanisms involving financial performance and leverage. This study provides critical insights for corporate managers, institutional investors, and policymakers on managing institutional ownership to improve company performance and value, and effectively handle financial leverage.